The Influence of Discipline, Responsibility, Cooperation, and Problem Awareness on Employability Skills - Budi Santosa; Pramudita Budiastuti; Purnawan Purnawan; Muhammad Sayuti (Jurnal Pendidikan Teknologi dan Kejuruan, 2021)
The purpose of this study was to analyze the influence of discipline, cooperation, responsibility, and problem awareness on employability skills individually and collectively. This study also aims to predict other factors that affect employability skills. The research method used correlational quantitative. Regression analysis was used to predict other factors that affect employability skills. The respondents consisted of 323 students from Muhammadiyah Vocational High Schools in Yogyakarta Province. The results showed that; (1) there is a significant effect between discipline and employability skills with an r-value of 0.588, (2) there is a significant influence between responsibility and employability skills with an r-value of 0.568, (3) there is a significant effect between collaboration and employability skills with an r-value of 0.501, (4) there is a significant effect between awareness of the problem and employability skills, with an r-value of 0.450, (5) there is a significant effect together between discipline, responsibility, cooperation, and awareness of the problem with employability skills with an r-value of 0.691.